(untitled) - Jesuthasan, Ravin (Boston, 2018)
Once the decision has been made to adopt automation and artificial intelligence technologies, leaders face difficult and stubborn questions about how to implement that decision: How, when, and where should we apply automation in our organizations? Is it a stark choice between humans versus machines? How do we stay on top of these technological trends as work and automation continue to evolve? Work and human capital experts Ravin Jesuthasan and John Boudreau argue that leaders need a new set of tools to answer these daunting questions. Going beyond traditional concepts like a "job," Jesuthasan and Boudreau show leaders that automation calls for a reexamination of what a job really is and show how to determine variations of tasks within jobs and then reconstruct those elements into new and different combinations. Furthermore, transcending the endless debate about humans being replaced by machines, the authors show how smart leaders instead are optimizing human-automation combinations that are not only more efficient but generate higher returns on improved performance. Based on groundbreaking primary research, this book provides an original, structured approach and a new set of tools for applying automation and artificial intelligence in your organization. Jesuthasan and Boudreau provide a practical four-step framework--deconstruct, optimize, automate, and reconfigure--through which you and others throughout your organization can collaborate to proactively and continuously "reconstruct" work and create optimal human-machine combinations.
Keywords: Đổi mới công nghệ,Technological innovations; Tham gia của nhân viên,Employee participation